2010
DOI: 10.1016/j.cell.2010.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Hair Cell-like Cells from Embryonic and Induced Pluripotent Stem Cells

Abstract: Summary Mechanosensitive sensory hair cells are the linchpin of our senses of hearing and balance. The inability of the mammalian inner ear to regenerate lost hair cells is the major reason for the permanence of hearing loss and certain balance disorders. Here we present a stepwise guidance protocol starting with mouse embryonic stem (ES) and induced pluripotent stem (iPS) cells, which were directed toward becoming ectoderm capable of responding to otic-inducing growth factors. The resulting otic progenitor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
286
3
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(312 citation statements)
references
References 65 publications
15
286
3
8
Order By: Relevance
“…Finally, other strategies for hearing restoration involve generation of hair cells in vitro from embryonic stem cells or induced pluripotent stem cells followed by reintroduction into the damaged ear. Some of these already rely on manipulation of FGF signaling to promote otic progenitor production (Oshima et al 2010;Chen et al 2012;Koehler et al 2013), but further consideration of FGF signaling levels at later stages of differentiation might be helpful in producing immature support cell progenitors that could be transplanted and then induced to differentiate in situ into hair cells.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, other strategies for hearing restoration involve generation of hair cells in vitro from embryonic stem cells or induced pluripotent stem cells followed by reintroduction into the damaged ear. Some of these already rely on manipulation of FGF signaling to promote otic progenitor production (Oshima et al 2010;Chen et al 2012;Koehler et al 2013), but further consideration of FGF signaling levels at later stages of differentiation might be helpful in producing immature support cell progenitors that could be transplanted and then induced to differentiate in situ into hair cells.…”
Section: Discussionmentioning
confidence: 99%
“…If such research is combined with genomic studies, it could lead to a very patientspecific prediction of whether a hearing loss is expected in a particular patient. Recently mouse studies have shown that the generation of inner ear sensory epithelia from pluripotent stem cells in 3D culture is possible and a protocol for obtaining hair cell-like cells with stereociliary bundles from iPS cells was announced (Oshima et al, 2010;Koehler et al, 2013).…”
Section: The Role Of Ips Cells As Potential Cures Of Hearing Loss In mentioning
confidence: 99%
“…[5]. Dans une perspective d'application à l'oreille interne, des recherches ont été entreprises pour induire in vitro la différen-ciation des CSE et iPS en cellules ciliées [6]. Ces recherches utilisent des lignées de CSE et iPS qui expriment le gène rapporteur codant pour la GFP (green fluorescent protein), sous le contrôle de l'amplificateur du gène Atoh1, gène dont l'expression est restreinte aux cellules ciliées dans l'oreille embryonnaire.…”
Section: Fabrication In Vitro D'épithéliums Sensoriels De L'oreilleunclassified
“…Ces recherches utilisent des lignées de CSE et iPS qui expriment le gène rapporteur codant pour la GFP (green fluorescent protein), sous le contrôle de l'amplificateur du gène Atoh1, gène dont l'expression est restreinte aux cellules ciliées dans l'oreille embryonnaire. Elles ont permis de définir les conditions in vitro de production de cellules ciliées fonctionnelles [6][7][8]. Très récemment, l'équipe du Pr Hashino (Université de l'Indiana, États-Unis) a franchi une étape supplémentaire importante en produisant un épithélium sensoriel de l'oreille interne à partir des CSE murines via une technologie de culture en 3D [9,10].…”
Section: Fabrication In Vitro D'épithéliums Sensoriels De L'oreilleunclassified